Estudo do escoamento turbulento em dutos corrugados com cavidade helicoidal - Rosa, Phillipe Mendes (2014)
Corrugated pipes have been used in several branches in the engineering, e.g, in transport flex line of oil in sea, where its installation, handling and remotion, become the process more practice due its flexibility. However, flow in corrugated pipes, in general, are subjects to an increase of drop pressure, an increase in the turbulence and deviations in the flow pattern as compared to the flow usually observed in pipes with constant cross section. In this sense, the present work shows an study both numerically and experimental of turbulent flow in corrugated pipes with helical grooves for different helix angles (or pitch) and Reynolds numbers varying between 7.500 and 100.000. The flow is modeled mathematically by the mass conservation and momentum equations, assuming the fluid is Newtonian and incompressible. To the flow, is applied the turbulence model of two equations, Baseline Model. The system equations resulted from mathematical modelling is discretized by using the element-based finite-volume method approach, and solved through the ANSYS-CFX. For the experimental part, is measured the friction factor in geometries equivalent to those studied numerically, where is performed by using the experimental facilities located in the LACIT/UTFPR. With the experimental data and numerical results, an correlation for friction factor is proposed in function of the geometric parameters of the corrugated pipe and Reynolds number, with an average uncertainty 0.88%. Moreover, is studied the groove's influence in the behavior of properties like fields of pressure, velocity, and stresses among another turbulent parameters. From the last analysis, has shown that the flow pattern near to the grooves follows the same behavior when it increases the Reynolds number and the grooves width, not showing qualitative changes when the helix angle has been changed.